Beam extraction of FFAG-based neutrino factory - Yokoi, T; Shirakabe, Y (2003)
FFAG-based neutrino factory employs cascaded FFAG rings. The beam injection and extraction are one of the crucial issues in the configuration. In the study, based on the ring parameters of a typical muon FFAG accelerator, a simple tracking simulation is carried out. (C) 2003 Elsevier Science B.V. All rights reserved.